(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
In recent decades, negative socio-economic and demographic tendencies have been observed in mountainous countries, especially in rural areas. The analysis of contemporary tendencies in demographic processes, namely – changes in the absolute number and natural growth of rural population, average density and age structure of the rural population in Armenia are given in the article. The most urgent problems connected with ongoing demographic processes have been identified and possible solutions have been indicated. The data published by the Statistical Committee of the RA for different years by regions and territories regarding de jure rural population, age structure, birth rate and mortality rate of villages in 37 districts of the country were used as base data. During 2001–2023 the absolute number of rural population of the RA decreased by 65.6 thousand or 5.7%. Among other factors, the reduction of the rural population was also resulted by negative migration saldo and negative trends in the demographic processes of the rural population. The reduction of rural population in the country was reflected in the growth of gross agricultural production. The reason for the latter is also the incomplete and partial use of tens of thousands of hectares of pastures and other agricultural lands due to the shortage of labor force, since the RA still has a low level of intensification. As of 2022, only 212.4 out of 443.4 thousand ha of plowed land or 47.9% were used. The rate of villages with population of up to 200 inhabitants increased by 1.8% (from 16.1 to 17.9%). The number of demographically more vulnerable villages with population of up to 500 inhabitants increased by 30, or by 9.5%. Natural growth rate of the rural population in 2021 compared to 2010 decreased by 3.1‰. During 2001–2022 the proportion of the rural population younger than working age decreased by 8.6%, and in absolute terms it made up 112.7 thousand people in the country. Due to the emerging unfavorable demographic processes, problems have arisen that impede the socio-economic development of rural areas of the Republic of Armenia. The outcomes can be used by the state and local level bodies for developing social and economic development programs of individual regions, municipalities, rural areas and settlements.